A sequência didática para o ensino do gênero jurídico no ensino médio na perspectiva do interacionismo sociodiscursivo - Gasperoni, Marcos Mendes Lisot Marthos (2023)
This research, in the area of Applied Linguistics, is anchored in studies of Socio-discursive Interactionism (SDI), by the Geneva Group, mainly represented by Jean-Paul Bronckart, Joaquim Dolz, Bernard Schneuwly and Michèle Noverraz, as well as by researchers from the Brazilian strand, aligned with the Group, such as Vera Lúcia Lopes Cristovão and Anna Rachel Machado, among others. The initial motivation, also justification for conducting the study, was the desire to contribute significantly to the teaching and meaningful learning of the Portuguese language by young people, originating the main question of the research: How can the Portuguese language discipline significantly promote the introduction of legal literacy in secondary education, in order to expand and improve the language skills of young people, preparing them for social practices in public and civic life? To answer this question, the general objective was to investigate the pertinence and potentialities of the didactic sequence procedure, within the scope of the SDI, as a theoretical-methodological approach, for the introduction of legal literacy in secondary education, with a view to expanding and improvement of young people's language skills and their preparation for the social practices of public and civic life. In order to achieve the general objective, the following specific objectives were outlined: 1) Investigate the habeas corpus genre, its structure and the teachable items, for the construction of a gender didactic model of it, in order to enable the elaboration of a specific didactic sequence; 2) Investigate, understand and analyze the development process of this didactic sequence, to highlight its pertinence and potential, to introduce legal literacy in high school, through the habeas corpus genre; 3) Seek evidence of the development and expansion of students' language skills in this process, as well as their engagement in legal literacy; 4) Analyze the students' final production, proposed in the didactic sequence, based on language skills, comparing them with the initial productions. The study, in line with the qualitative-naturalistic approach (ANDRÉ, 2009), was carried out in a 3rd year high school class at a public school in the interior of the state of Rio Grande do Sul, Brazil. Initially, the structure and teachable items of the habeas corpus genre were investigated for the construction of a didactic model of gender. Based on this model, a didactic sequence was prepared for teaching habeas corpus, for a pedagogical intervention (DAMIANI, et al. 2013) in the class. The performance of the pedagogical intervention, recorded in daily notes and audio recordings, for data generation, allowed the investigation, understanding and analysis of the development of the didactic sequence. The activities carried out in the didactic sequence showed the evolution of the students' language skills with regard to the habeas corpus legal genre. The comparison between the initial production and the final production, as data generation instruments, demonstrated the introduction to legal literacy by these students, as more than 86.7% (26 students) of the class created a genre that was appropriate for the communication situation. Therefore, the results show the significant potential of the didactic sequence, as a planning model for the didactics and teaching of textual genres. Furthermore, the study reinforces the contributions of the SDI, as a linguistic theoretical framework that encompasses socio-historical and cultural issues, in addition to cognitive and psychological aspects; these contributions can be verified in the comparisons between the initial and final productions, regarding the expansion of students' abilities in language activities.